2012
DOI: 10.4236/ape.2012.21003
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education in Kindergarten Promotes Fundamental Motor Skill Development

Abstract: Skill development is influenced by many factors and, among many, opportunity of practice and appropriate instruction provided by teacher might be considered as key elements but still need to be empirically investigated. Therefore, the purpose of this study was to compare gross motor development of young children enrolled in physical education, provided by a specialist teacher, and children enrolled in recreational activities, provided by a regular teacher, in kindergarten. Fifty children were divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
31

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 13 publications
3
48
0
31
Order By: Relevance
“…Not only the amount of minutes spent, but also the amount of time spent with appropriate training and supervision (which include instruction and feedback) is considered the key for the motor development [30]. Lemos, Avigo and Barela [31] reported that subject who had physical education class supervised by a physical education teacher had superior MC when compared with those without a trained teacher, which support the importance of the quality spent in practice that aim improvement in MC rather just the amount spent.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the amount of minutes spent, but also the amount of time spent with appropriate training and supervision (which include instruction and feedback) is considered the key for the motor development [30]. Lemos, Avigo and Barela [31] reported that subject who had physical education class supervised by a physical education teacher had superior MC when compared with those without a trained teacher, which support the importance of the quality spent in practice that aim improvement in MC rather just the amount spent.…”
Section: Discussionmentioning
confidence: 99%
“…Especula-se tal resultado, sugerindo que o ambiente da escola particular proporciona um contexto instrucional mais propício para o desenvolvimento da competência motora. Não só uma estrutura física favorável do ambiente da escola particular deve ser considerada, mas também a disponibilidade e acesso a equipamentos de jogos, participação em esportes e aulas de educação física com especialistas devem ser interpretados como fatores que podem influenciar o desenvolvimento da competência motora (Giagazoglou et al, 2008;Lemos, Avigo, & Barela, 2012;Queiroz, Re, Henrique, Moura, & Cattuzzo, 2014;Timmons, Naylor, & Pfeiffer, 2007).…”
Section: Resultsunclassified
“…Tal resultado foi percebido tanto em habilidades de locomoção quanto em habilidades de controle de objetos. Este resultado é mais contundente que outros estudos, os quais encontraram diferenças significativas apenas em habilidades básicas que envolviam controle de objetos 34,35 . No entanto, mesmo que este estudo apresente a limitação de ter sido empregado um delineamento de corte transversal, os resultados, assim como estudos prévios, levam a inferir que o contexto das aulas de educação física talvez não tem sido suficiente para as crianças apresentarem desempenho motor proficiente nas habilidades básicas de locomoção 15 e controle de objetos 17 .…”
Section: Discussionunclassified